THE APPLICATION OF INTERACTIVE GAME TEACHING METHOD FOR ENGLISH SPEAKING SKILL OF GRADE 6 STUDENTS IN SICHUAN PROVINCE, CHINA - Liu, Jia; Sakulwongs, Nipaporn (Academic Journal Phranakhon Rajabhat University, 2023)
This study compared grade 6 students’ English speaking ability before and after using an Interactive Game Teaching Method and investigated their satisfaction with the use of an Interactive Game Teaching Method in an English-speaking course in Sichuan Province, China. The sample group consisted of 30 grade 6 students from Sichuan Province, China. Quantitative data was collected through 4 lesson plans, a pretest, a posttest, and a questionnaire. It was analyzed using means, standard deviations, and paired sample t-test. The data collection lasted for 4 weeks and the teaching experiment was conducted online due to the pandemic. The results of the pretest and post-test showed that the students in the sample group improved their language-speaking skills with a pretest score (x̅=22.03, SD=4.48) and a post-test score (x̅=28.97, SD=4.06). The data collected from the questionnaire indicated that all items were rated highly. The majority of students in the sample group expressed positive satisfaction with the use of the Interactive Game Teaching Method in learning English. This study demonstrated that the use of the Interactive Game Teaching Method provided an alternative and effective method for learning English.